Early Life Stress Promotes Heroin Seeking But Does Not Alter the Excitability of Insular Pyramidal Cells Targeting the Nucleus Accumbens - Leyrer-Jackson, Jonna M.; Overby, Paula F.; Nagy, Erin K.; Olive, M. Foster (Frontiers in Behavioral Neuroscience, 2021)
A number of retrospective studies have demonstrated adverse childhood experiences are associated with increased vulnerability to substance use disorders, including opioid use disorders (OUDs). These adverse childhood experiences, also referred to as early life stress (ELS), can be modeled in laboratory animals by various paradigms including limited bedding and nesting (LBN) procedures. Studies using rodent models of ELS have been shown to recapitulate various aspects of OUDs, including relapse propensity and perseverance of drug-seeking behavior. In the current study, we utilized the LBN paradigm to explore potential effects on heroin self-administration, extinction, and relapse-like behaviors in male and female rats. We also utilized in vitro whole-cell electrophysiology to examine the effects of LBN and repeated heroin administration on excitability of pyramidal neurons in the anterior insular cortex (AIC) projecting to the nucleus accumbens core (NAc), as recent studies suggest that this circuit may mediate various aspects of OUDs and may be compromised as a result of either ELS or OUDs. We observed that compared to control animals, rats exposed to LBN conditions during postnatal days 2-9 showed increased breakpoints for heroin self-administration under a progressive ratio schedule of reinforcement, impaired extinction of heroin-seeking behavior, and increased reinstatement of heroin-seeking behavior induced by heroin-associated cues. No effect of LBN rearing conditions were observed on the acquisition and maintenance of heroin self-administration, and no sex differences in heroin intake were observed. LBN and control reared animals showed no differences in the excitability of AIC-NAc pyramidal neurons, but animals treated with repeated heroin showed decreased excitability of these neurons through a significant increase in rheobase and reduction in action potentials induced by depolarizing currents. Together, these results suggest that ELS exposure produces exacerbations of heroin seeking behavior without parallel effects on AIC-NAc excitability, although heroin itself reduces the excitability of these neurons.